Case Studies in Global School Health Promotion From Research to Practice - Aldinger, Carmen E.; Vince Whitman, Cheryl; SpringerLink (Online service) (New York, NY : Springer New York, 2009)
Case Studies in Global School Health Promotion Cheryl Vince Whitman and Carmen Aldinger A growing body of research identifies strong links between children$1 (Bs health, social and educational outcomes; it also notes the reciprocal benefits of access to quality education on individual and family health status. In response to these findings, the World Health Organization developed the concept of the Health-Promoting School (HPS), a living catalyst for healthy lives, and for positive changes that students can take home and into the community. Case Studies in Global School Health Promotion provides readers with a theoretical and research base needed to understand the methods used in communities all over the world to put this captivating concept in place. Case examples from over two dozen countries (representing urban and rural areas in developing and developed nations) outline the strategies taken to implement HPS programs in individual schools, municipalities, and nations. For each program, case study authors explain the problems they tackled, their motivation and supports to respond creatively; and the barriers they faced. In the cases, authors describe the capacities and infrastructure they created and mechanisms for cooperation; as well as the personnel, financial, and time requirements involved. Case studies were drawn from the following regions: Africa The Americas Europe Eastern Mediterranean South and Southeast Asia Western Pacific Case Studies in Global School Health Promotion offers a world of insights, ideas, and guidance to those addressing social determinants of health at this formative stage, including: education and health policy makers; professionals and administrators; and researchers in national governments, universities, local schools, community, non-governmental organizations and civil society. The material provides interesting and useful information to those dedicated to these issues within WHO, FRESH (Focus Resources on Effective School Health) Partners and other United Nations agencies. It is also an instructive text for graduate students in public health, education, allied health professions and social sciences.s
Section 1. Introduction and Overview of Findings -- Introduction and Background -- Framing Theories and Implementation Research -- Overview of Findings from Case Study Analysis -- Section 2. Case Studies -- Africa -- Kenya: Action-Oriented and Participatory Health Education in Primary Schools -- Mauritius: Health Promotion for Youth -- Nigeria: Health-Promoting Schools -- South Africa: Sapphire Road Primary -- The Americas -- Barbados: School Health Case Study -- Brazil: Addressing the Social Determinants of Health: The Experience of a Municipal School in Rio de Janeiro -- Canada: Case Study -- Nicaragua: The Social 'Treasure' of Participation -- United States of America: The Michigan Journey Toward Coordinated School Health -- Uruguay: Mainstreaming Health Promotion in Education Policies -- Europe -- Germany: Anschub.de$1 (B'Alliance for sustainable school health and education' -- Kosovo: A Health-Promoting Schools Approach to Reduce the Risks of Lead Poisoning and to Establish Cross-Ethnic Collaboration -- Poland: The Health-Promoting School National Certificate -- Scotland: Sustaining the Development of Health-Promoting Schools$1 (BThe Experience of Scotland in the European Context -- Eastern Mediterranean -- Bahrain: National Comprehensive School Health Program, Health-Promoting Schools -- Oman: Health-Promoting Schools$1 (BCollaboration and Investment -- United Arab Emirates: Health-Promoting Schools$1 (BStrategies for Policy Change -- South and Southeast Asia -- China: Implementing Health-Promoting Schools inZhejiang Province, China -- Hong Kong: Health-Promoting Schools -- India: Implementing Health-Promoting Schools$1 (BHOPE Initiative -- Lao PDR: Strengthening the School Health Initiative -- Philippines: Supporting Health Promotion in Schools Through the Urbani School Health Kit -- Singapore: Health-Promoting Schools$1 (BThe CHERISH Award -- Viet Nam -- Western Pacific -- Australia: The New South Wales School-Link Initiative -- Cook Islands: The 'Strengthening Project'.s
Keywords: Medicine; Public health; Health promotion; Maternal and child health services; Health administration; Medicine & Public Health; Public Health; Health Administration; Health Promotion and Disease Prevention; Maternal and Child Health; Electronic books